The First Century of Hungarian Khitanology - Apatóczky, Ákos; Szilágyi, Zsolt (Acta Mongolica, 2022)
Hungarian scholarship has traditionally shown a deep interest in East Asian philology, and as a result has achieved several significant results in this field. Ever since the first written records of the Khitan (formerly also known as "kitaj" in Hungarian literature) were discovered at the beginning of the 20th century, Hungarian philologists have paid particular attention to these discoveries. The first scientific article on the subject in Hungarian was a 1927 study by Lajos (Louis) Ligeti. In this paper, we would like to give an overview of almost a century of research on the Khitans in Hungary.